Extraction, purification and characterization of lipoxygenase from Pleurotus ostreatus. - Abdullah, Qabass; AL-Jibori, Mona; AL-Arrji, Sanad (Iraqi Journal of Science, 2023)
Lipoxygenase was extracted from the cup of Pleurotus ostreatus ( Jaq : Fr ) oyster mushroom for the first time in Iraq, and purified homogeneously through precipitation with 40% saturation of (NH4)2SO4 as a partial purification then loaded on DEAE-Cellulose (Diethyl amino ethyl Cellulose) ion-exchange chromatography column and then the highly active elution parts have been passed through gel filtration column with Sephacryl S-300 as a final purification with 804 (U/mg protein) specific activity, 11.32 fold of purification and 36.54% yield . The molecular weight of the enzyme was estimated to 74 KDa by gel filtration Sephacryl S-300 column and the isoelectric point for enzyme was 5.3. The optimal pH for lipoxygenase activity and stability were 8 and 6-8.5 respectively, and the optimal temperature for the activity and stability of the enzyme were 30 and 10-45 respectively. Also the activation energy necessary for Lipoxygenase to convert lionleic acid to product and for enzyme denaturalization were calculated to 9.674 and 28.087 Kilo calorie/mole respectively.